ESTIMASI TITIK UBAH TUNGGAL PADA REGRESI LINIER DENGAN SATU PEUBAH BEBAS - Muhammad Bayu Nirwana; Dewi Wulandari (Universitas Muhammadiyah Semarang, 2018)
Linear regression is a statistical method for estimating a linear relationship between one dependent variable and one or more independent variables. In simple linear regression, relationship analysis is carried out between one dependent variable and one independent variable to obtain a linear equation. The linear equation can then be used to predict the value of the dependent variable, if the value of the independent variable is known. The use of linear regression encounters a problem when the linear relationship between dependent variables and independent variables changes at a certain point. Segmentation regression is a regression model in which the relationship between variables is bound to independent variables in the form of piecewise linear relationships. The relationship is represented by two or more straight lines connected in a certain threshold value called a breakpoint. In this paper we will discuss the single breakpoint estimation in simple linear regression. Keywords: linear regression, segmented regression, single breakpoint